Numerical Assessment of Infragravity Swash Response to Offshore Wave Frequency Spread Variability. Issue 9 (10th September 2019) - Ruju, Andrea; Lara, Javier L.; Losada, Inigo J.
Abstract: We use a numerical model, already validated for this purpose, to simulate the effect of wave frequency spread on wave transformation and swash amplitudes. Simulations are performed for planar beach slope cases and for offshore wave spectra whose frequency spread changes over realistic values. Results indicate that frequency spread, under normally approaching waves, affects swash amplitudes. For moderately dissipative conditions, the significant infragravity swash increases for increasing values of the offshore frequency spread. The opposite occurs under extremely dissipative conditions. The numerical analysis suggests that this inverted pattern is driven by the effect that different distributions of incoming long‐wave energy have on low‐frequency wave propagation and dissipation. In fact, with large frequency spreads, wave groups force relatively short subharmonic waves that are strongly enhanced in the shoaling zone. This process leads to an infragravity swash increase for increasing frequency spread under moderately dissipative conditions in which low‐frequency energy dissipation in shallow water is negligible or small. However, under extremely dissipative conditions, the significant low‐frequency energy dissipation associated with large frequency spreads overturns the strong energy growth in the shoaling zone eventually yielding an infragravity swash decrease for increasing frequency spread. Key Points: Numerical simulations reveal that frequency spread affects swash amplitudes with a pattern that inverts over two Iribarren number ranges An infragravity swash increase for increasing frequency spread is observed under moderately dissipative conditions The infragravity swash increases for decreasing frequency spread under extremely dissipative conditions